2009
DOI: 10.1007/bf03346503
|View full text |Cite
|
Sign up to set email alerts
|

A low reported energy intake is associated with metabolic syndrome

Abstract: The results of this study support the hypothesis that subjects with MS have an energy-sparing metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…These results are consistent with our previous observations that found that people with metabolic syndrome have a daily intake of nutrients that is similar to that of people without metabolic syndrome. 36 It is likely that larger cohorts will be needed to undertake such analysis. Yet, we cannot exclude the possibility that more complex interactions than those of diet alone are present when insulin resistance becomes part of the metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with our previous observations that found that people with metabolic syndrome have a daily intake of nutrients that is similar to that of people without metabolic syndrome. 36 It is likely that larger cohorts will be needed to undertake such analysis. Yet, we cannot exclude the possibility that more complex interactions than those of diet alone are present when insulin resistance becomes part of the metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The current results illustrated that the inadequate dietary EI was associated with high prevalence of HMetS in different sub-groups. In a study conducted in Italy, the authors found that patients with MetS reported lower energy intake than those without MetS [ 76 ]. This suggested that MetS diagnosed by Harmonizing Metabolic Syndrome criteria is more sensitive than AACE-MetS in relation to energy intake.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects completed a 3-day food record, a tool commonly used to assess dietary information in cardiac patients (Buscemi et al, 2009; Dunbar et al, 2013; Harton, Narojek, & Solik-Tomassi, 2005; Jungert & Neuhauser-Berthold, 2013; McNeil et al, 2013; Murray et al, 2013; Thiengwiboonwong, Chongsuwat, Temcharoen, Pandii, & Pavadhgul, 2013; Thomas, Ziogas, Yan, Schmitz, & LaFontaine, 1998; Watson et al, 2002). Then the daily sodium intake based on the food diaries was analyzed and computed using the Minnesota Nutrition Data System (V 5.0/35; Center, 1992).…”
Section: Methodsmentioning
confidence: 99%